Hubungan Stunting dengan Prestasi Belajar Anak Sekolah Dasar di Kecamatan Tikala Manado - Gunawan, Gregorius; Manoppo, Jeanette I. Ch.; Wilar, Rocky (e-CliniC, 2018)
Abstract: Stunting is a condition where height is not in accordance with age. It is due to chronic malnutrition which causes nonoptimal brain development that can affect childrenâ€™s cognitive development, performance at school, and learning ability, as well as consequently influences learning achievement at school. This study was aimed to identify the correlation between stunting and learning achievement of elementary school students at Tikala Manado. This was an analytical study with a cross sectional design. Respondents were elementary school students at Tikala Manado aged 7-13 years that had their average grades. Data were analyzed by using unpaired T-test. The results showed that there were 232 students as respondents. Stunting was found in 103 students (44%) and not stunting in 129 students (56%). The average grade of stunting students was 67.16 and of not stunting students was 68.53. Statistical analysis showed that there was no significant difference between the average student grade in stunting students and not stunting students (P=0.215; Î±=0.05). Conclusion: There was no significant correlation between stunting and learning achievementKeywords: stunting, learning achievementÂ Abstrak: Stunting merupakan keadaan dimana tinggi badan tidak sesusai dengan usia. Hal ini dapat menyebabkan perkembangan otak tidak optimal sehingga berpengaruh pada perkem-bangan kognitif dan performance anak di sekolah, serta kemampuan belajar, yang selanjutnya berpengaruh pada prestasi belajar anak di sekolah. Penelitian ini bertujuan untuk mengetahui hubungan stunting dan prestasi belajar pada siswa Sekolah Dasar di Kecamatan Tikala Manado. Jenis penelitian ialah analitik dengan desain potong lintang. Responden ialah siswa sekolah dasar di Kecamatan Tikala Manado yang berusia 7-13 tahun dan rerata nilai rapor siswa. Analisis uji statistik yang digunakan ialah uji T-test tidak berpasangan. Hasil penelitian mendapatkan 232 siswa sebagai responden. Stunting didapatkan pada 103 siswa (44%) dan yang tidak stunting 129 siswa (56%). Rerata nilai rapor pada siswa stunting 67,16 dan yang tidak stunting 68,53. Hasil uji analisis menunjukkan tidak terdapat perbedaan rerata prestasi belajar antara siswa stunting dan tidak stunting (P=0,215; Î±=0,05). Simpulan: Tidak terdapat hubungan bermakna antara stunting dan prestasi belajar.Kata kunci: stunting, prestasi belajar